2013
DOI: 10.1101/sqb.2013.78.020339
|View full text |Cite
|
Sign up to set email alerts
|

The "Histone Mimicry" by Pathogens

Abstract: One of the defining characteristics of human and animal viruses is their ability to suppress host antiviral responses. Viruses express proteins that impair the detection of viral nucleic acids by host pattern-recognition receptors, block signaling pathways that lead to the synthesis of type I interferons (IFN) and other cytokines, or prevent the activation of virus-induced genes. We have identified a novel mechanism of virus-mediated suppression of antiviral gene expression that relies on the presence of histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…In support of this model, we found that both the histone H3 tail and the H3N2 NS1 tail bind in a sequence-dependent fashion to the polymerase-associated factor 1 (Paf1) component of the Paf1 complex that contributes to RNA elongation as well as other cotranscriptional processes (Marazzi et al, 2012). As expected, the NS1 tails from influenza H5N1 (Marazzi et al, 2012) and H1N1 (Schaefer et al, 2013) that lack the histone mimic did not bind to Paf1.…”
Section: Histone Mimicry By Influenza Virusessupporting
confidence: 76%
“…In support of this model, we found that both the histone H3 tail and the H3N2 NS1 tail bind in a sequence-dependent fashion to the polymerase-associated factor 1 (Paf1) component of the Paf1 complex that contributes to RNA elongation as well as other cotranscriptional processes (Marazzi et al, 2012). As expected, the NS1 tails from influenza H5N1 (Marazzi et al, 2012) and H1N1 (Schaefer et al, 2013) that lack the histone mimic did not bind to Paf1.…”
Section: Histone Mimicry By Influenza Virusessupporting
confidence: 76%
“…We focused primarily on di-methylation of lysine 126 on LIG1 (LIG1K126me2), as it had the highest affinity of the LIG1K126 methyl orders for full-length UHRF1 and was reported to be the predominant methyl form in several cell types [ 21 ]. The amino acids surrounding LIG1K126 resemble those around H3K9, earning LIG1 the title of “histone-mimic”, a term first used to describe short linear motifs shared between histone H3 and viral proteins [ 23 ]; these motifs are present in various chromatin-related proteins [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histone mimicry is used by certain viruses to subvert normal host defenses 33 . For instance, the influenza non-structural protein 1 from the H3N2 subtype uses the histone H3K4-like sequence 226ARSK229 at its carboxyl terminus to bind to and hijack the human PAF1 transcription elongation complex (HPAF1C), thus affecting the expression of antiviral genes 34 .…”
Section: Discussionmentioning
confidence: 99%